Effects of sprint and plyometrics training on field sport acceleration technique - Lockie, R. G.; Murphy, A. J.; Callaghan, S. J.; Jeffriess, M. D. (The Journal of Strength and Conditioning Research, 2014)
The mechanisms for speed performance improvement from sprint training and plyometrics training, especially relating to stance kinetics, require investigation in field sport athletes. This study determined the effects of sprint training and plyometrics training on 10-m sprint time (0-5, 5-10, and 0-10 m intervals), step kinematics (step length and frequency, contact and flight time), and stance kinetics (first, second, and last contact relative vertical [VF, VI], horizontal [HF, HI], and resultant [RF, RI] force and impulse; resultant ground reaction force angle [RFO]; ratio of horizontal to resultant force [RatF]) during a 10-m sprint. Sixteen male field sport athletes were allocated into sprint training (ST) and plyometrics training (PT) groups according to 10-m sprint time; independent samples t-tests (p < 0.05) indicated no between-group differences. Training involved 2 sessions per week for 6 weeks. A repeated measures analysis of variance (p < 0.05) determined within- and between-subject differences. Both groups decreased 0-5 and 0-10 m time. The ST group increased step length by ~15%, which tended to be greater than step length gains for the PT group (~7%). The ST group reduced first and second contact RF? and RatF, and second contact HF. Second contact HI decreased for both groups. Results indicated a higher post-training emphasis on VF production. Vertical force changes were more pronounced for the PT group for the last contact, who increased or maintained last contact VI, RF, and RI to a greater extent than the ST group. Sprint and plyometrics training can improve acceleration, primarily through increased step length and a greater emphasis on VF.